EKSPLORASI KEBIJAKAN BAHASA DAN PENDIDIKAN NASIONAL INDONESIA - Madinah, Nur; Sabilila, Adezoya Shifa; Khanifah; Panggeda, Adam Sayid; Muasomah; Mukhlis, Abdul (CV. Kalimasada Group, 2025)
This article aims to explore the close relationship between language policy and national education in Indonesia as two fundamental components in shaping the direction of national development. The language policy discussed includes aspects of language planning, development, fostering, and protection, which include Indonesian as the national language, regional languages as cultural heritage, and foreign languages as a means of global communication. The implementation of the language policy covers various domains, such as mass media, formal and non-formal education systems, the judicial system and public administration, and international relations. This study uses a descriptive qualitative approach strengthened by an in-depth literature study method. This study examines various policy documents, previous research results, government regulations, and the thoughts of language and education experts. The results of the study show that language and education policies are dynamically interrelated in forming the nation's collective identity, strengthening nationalism, and equipping students with language and character competencies that are relevant to the demands of the times. Language policies that are integrated into the education system can improve students' literacy skills, enrich national insight, and foster an attitude of tolerance towards cultural diversity and local languages.